1999
DOI: 10.1074/jbc.274.25.18067
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Substrate 1-induced Inhibition of Endoplasmic Reticulum Ca2+ Uptake in β-Cells

Abstract: To understand the role of the insulin receptor pathway in ␤-cell function, we have generated stable ␤-cells (␤IRS1-A) that overexpress by 2-fold the insulin receptor substrate-1 (IRS-1) and compared them to vector-expressing controls. IRS-1 overexpression dramatically increased basal cytosolic Ca 2؉ levels from 81 to 278 nM, but it did not affect Ca 2؉ response to glucose. Overexpression of the insulin receptor also caused an increase in cytosolic Ca 2؉ . Increased cytosolic Ca 2؉ was due to inhibition of Ca 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 56 publications
5
43
0
Order By: Relevance
“…Our data have shown that insulin-stimulated insulin secretion is mediated by functional insulin receptors (18), IRS-1, and PI3-K activation. Activation of these substrates by insulin in ␤-cells has previously been reported (16,19), and our results illustrate that these effects are directly linked to insulin secretion and increases in [Ca 2ϩ ] i . The increase in [Ca 2ϩ ] i evoked by insulin appears to be mediated by release of Ca 2ϩ from intracellular Ca 2ϩ stores based on the localization of the increase, the effects of thapsigargin, and the occurrence of [Ca 2ϩ ] i changes in the absence of extracellular Ca 2ϩ .…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Our data have shown that insulin-stimulated insulin secretion is mediated by functional insulin receptors (18), IRS-1, and PI3-K activation. Activation of these substrates by insulin in ␤-cells has previously been reported (16,19), and our results illustrate that these effects are directly linked to insulin secretion and increases in [Ca 2ϩ ] i . The increase in [Ca 2ϩ ] i evoked by insulin appears to be mediated by release of Ca 2ϩ from intracellular Ca 2ϩ stores based on the localization of the increase, the effects of thapsigargin, and the occurrence of [Ca 2ϩ ] i changes in the absence of extracellular Ca 2ϩ .…”
Section: Discussionsupporting
confidence: 52%
“…This report also showed that insulin could evoke an increase in intracellular [Ca 2ϩ ] ([Ca 2ϩ ] i ). A recent study with clonal ␤-cells demonstrated that overexpression of IRS-1 and insulin receptor elevated [Ca 2ϩ ] i levels and enhanced fractional insulin secretion (19), in good agree-ment with the studies on application of exogenous insulin.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…This might imply a reconstruction of the ER from pre-existing SERCA2b-and InsP $ -RI-associated intracellular Ca# + stores towards additional SERCA3-and InsP $ -RII-and III-associated ER subcompartments in connection with plasma membrane. Again, this new ER network may be needed to create links between agonists and their fine spatial tuning of Ca# + -dependent signalling processes, as shown recently for SERCA and insulin-receptor substrate, IRS-1 [53].…”
Section: Discussionmentioning
confidence: 96%
“…Experiments performed with a ␤-cell tumor line derived from IRS1 -/-mice have revealed that insulin stimulation fails to elevate cytosolic Ca 2+ in these IRS-1-deficient cells; insulin evokes release of intracellular cell stores of Ca 2+ in wild-type transformed ␤-cells (39). Interestingly, studies in the INS-1 ␤-cell line have demonstrated that overexpression of IRS-1 increases cytosolic Ca 2+ levels due to inhibition of uptake by the endoplasmic reticulum (40). Owing perhaps to this dysregulation of intracellular Ca 2+ , insulin secretion was increased two-fold in INS cells.…”
Section: Irs-1 Pathways In ␤-Cells: a Link To Insulin Secretion?mentioning
confidence: 99%